A qualitative study on couples' attitudes and concerns regarding a freeze all strategy in ART treatment. (8th August 2022) - Sylvest, Randi; Stormlund, Sacha; Koert, Emily; Freiesleben, Nina la Cour; Løssl, Kristine; Ziebe, Søren; Schmidt, Lone; Pinborg, Anja
Abstract: The freeze all strategy has become a promising alternative to fresh embryo transfer in fertility treatment almost eliminating late ovarian hyperstimulation syndrome (OHSS) in the segmented cycle. There is a lack of in-depth knowledge regarding patients' attitudes towards the freeze all strategy. The aim of this study was to explore the attitudes towards a freeze all strategy compared with fresh embryo transfer in assisted reproductive technology (ART) treatment among couples in a public health care setting. We conducted semi-structured qualitative interviews with ten couples already participants in a randomised controlled trial (RCT) and undergoing ART treatment. The couple's responses showed five themes: (i) Starting treatment provides needed relief; (ii) Treatment must be provided with humanity; (iii) Provision of information instigates positive attitudes towards treatment; (iv) Fresh treatment – 'The normal way'; and (v) Freeze all treatment – 'The new black'. When thorough information about treatment procedures and safety aspects regarding both the freeze all and fresh embryo transfer strategy is given prior to initiation of treatment, couples feel secure and content, regardless of which treatment strategy is finally applied. This qualitative study found that starting treatment could prompt longed-for relief, as professionals would now 'take over' and assist in meeting the couple's family building goals.